Multifocal Tumorous Pseudoangiomatous Stromal Hyperplasia Presenting as Asymmetric Bilateral Breast Enlargement - Vasconcelos, I.; Perez Fernandez, C. M.; Günzel, S.; Schoenegg, W. (Geburtshilfe und Frauenheilkunde, 2015)
PASH is a benign proliferation of stromal myofibroblasts that affects mostly premenopausal women and typically shows estrogen and progesterone receptor expression, allowing speculation regarding a hormonal cause. It usually presents as an incidental finding on a mammogram or as a palpable mass. We present a case of diffuse asymmetrical massive breast enlargement in a premenopausal woman with history of previous multiple PASH excisions for recurrent lesions, caused by multifocal tumorous PASH virtually replacing the breast parenchyma. Immunohistochemistry examination showed no hormone receptor expression. Despite its benign nature, such presentation of PASH is managed with bilateral mastectomy and immediate reconstruction with expanders for cosmetic and comfort reasons, while tumor excision or expectant management is deemed to lead to recurrence and progression. Although a hormonal origin is speculated based on hormone expression studies and typical patient profile, this case showed 0 % estrogen/progesterone expression in the final histology specimen.
Keywords: benign mammary gland tumor; hormonal receptor; breast